ANALISIS PENANDA STILISTIKA DALAM SURAT AT-TIIN - A Dzo'ul Milal (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2008)
Stylistics is the study of language combining linguistic and literary approaches. It deals mainly with analyzing linguistic features used in literary works. Al Qur’an viewed as a literary work produced by Allah, the Almighty, uses miraculous stylistic devices which no single human being is capable of revealing His true intention. This paper, therefore, is just to make approximate interpretation of some stylistic devices which are used in one of the Surahs in Al Qur’an called At Tiin. Using some theories of stylistics, the writer finds some devices used in that surah, namely the speech act of swearing using some history-related words, the syntactic device of emphatic form, paradox, the use of surprise and rhetorical questions, balanced lexical items, and rhymes. Those devices are exerted to produce more effective messages to convince the readers about the contents being conveyed.